Interfacial Tensions of Ethoxylated Fatty Acid Methyl Ester Solutions Against Crude Oil. Issue 4 (22nd May 2017) - Liu, Miao; Fang, Hongbo; Jin, Zhiqiang; Xu, Zhicheng; Zhang, Lei; Zhang, Lu; Zhao, Sui
Abstract: The dynamic interfacial tension (IFT) of ethoxylated fatty acid methyl ester solutions against n ‐alkanes, kerosene, and diluted heavy oil have been investigated by spinning drop interfacial tensiometry. The influences of ethylene oxide (EO) groups and alkyl chain length on IFT were investigated. The experiment results show that the water solubility decreases with an increase in alkyl chain length or a decrease in EO groups. The ability to lower the interfacial tension against hydrocarbons improves with both increasing alkyl chain length and EO group at the best hydrophilic‐lipophilic balance, which can be attributed to the enhancement of the interfacial hydrophobic interactions and the rearrangement of interfacial surfactant molecules. The mixed adsorption of surfactant molecules and surface‐active components may reduce IFT to a lower value. C18 =E3 shows the best synergism with surface‐active components. However, the IFT values against pure crude oil are obviously higher than those against hydrocarbons, which may be caused by the nature of heavy oil.